America and the just war tradition: a history of U.S. conflicts - Hall, Mark David; Charles, J. Daryl; Johnson, James Turner (University of Notre Dame Press, 2019)
America and the Just War Tradition examines and evaluates each of America’s major wars from a just war perspective. Using moral analysis that is anchored in the just war tradition, the contributors provide careful historical analysis evaluating individual conflicts. Each chapter explores the causes of a particular war, the degree to which the justice of the conflict was a subject of debate at the time, and the extent to which the war measured up to traditional ad bellum and in bello criteria. Where appropriate, contributors offer post bellum considerations, insofar as justice is concerned with helping to offer a better peace and end result than what had existed prior to the conflict. This fascinating exploration offers policy guidance for the use of force in the world today, and will be of keen interest to historians, political scientists, philosophers, and theologians, as well as policy makers and the general reading public.